Differential Role of Rapamycin and Torin/KU63794 in Inflammatory Response of 264.7 RAW Macrophages Stimulated by CA-MRSA - Rebekah K. H. Shappley; Thomas Spentzas (International Journal of Inflammation)
Background. Rapamycin suppresses the RAW264.7 macrophage mediated inflammatory response but in lower doses induces it. In the present study, we tested the suppression of the inflammatory response in the presence of mTOR 1 and 2 inhibitors, Torin and KU63794. Methods. RAW264.7 cells were stimulated for 18 hrs with 106 to 107 CFU/mL inocula of community-acquired- (CA-) MRSA isolate, USA400 strain MW2, in the presence of Vancomycin. Then, in sequential experiments, we added Torin, KU63794, and Rapamycin alone and in various combinations. Supernatants were collected and assayed for TNF, IL-1, IL-6, INF, and NO. Results. Rapamycin induces 10–20% of the inflammatory cascade at dose of 0.1 ng/mL and suppresses it by 60% at dose of 10 ng/mL. The induction is abolished in the presence of Torin KU63794. Torin and KU63794 are consistently suppressing cytokine production 50–60%. Conclusions. There is a differential response between Rapamycin (mTOR-1 inhibitor) and Torin KU63794 (mTOR 1 and 2 inhibitors). Torin and KU63794 exhibit a dose related suppression. Rapamycin exhibits a significant induction-suppression biphasic response. Knowledge of such response may allow manipulation of the septic inflammatory cascade for clinical advantages.